Cell‐based strategies for vascular regeneration. Issue 5 (10th February 2016) - Zou, Tongqiang; Fan, Jiabing; Fartash, Armita; Liu, Haifeng; Fan, Yubo
Abstract: Vascular regeneration is known to play an essential role in the repair of injured tissues mainly through accelerating the repair of vascular injury caused by vascular diseases, as well as the recovery of ischemic tissues. However, the clinical vascular regeneration is still challenging. Cell‐based therapy is thought to be a promising strategy for vascular regeneration, since various cells have been identified to exert important influences on the process of vascular regeneration such as the enhanced endothelium formation on the surface of vascular grafts, and the induction of vessel‐like network formation in the ischemic tissues. Here are a vast number of diverse cell‐based strategies that have been extensively studied in vascular regeneration. These strategies can be further classified into three main categories, including cell transplantation, construction of tissue‐engineered grafts, and surface modification of scaffolds. Cells used in these strategies mainly refer to terminally differentiated vascular cells, pluripotent stem cells, multipotent stem cells, and unipotent stem cells. The aim of this review is to summarize the reported research advances on the application of various cells for vascular regeneration, yielding insights into future clinical treatment for injured tissue/organ. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 1297–1314, 2016.